Do high-risk features support the use of adjuvant chemotherapy in stage II colon cancer? A Turkish Oncology Group study - (:unkn) unknown (Il Pensiero Scientifico Editore s.r.l., 2014)
Background. A high-risk group of patients with stage II colon cancer has been identified by the results of studies in Western populations. The aim of this study was to investigate the prognostic factors of adjuvant chemotherapy in Turkish patients with stage II colon cancer. Methods. A total of 554 stage II colon cancer patients were retrospectively enrolled in the study. Three hundred fifty-three patients had received adjuvant chemotherapy (5-FU-LV, FOLFOX or FLOX) and 201 had received no adjuvant chemotherapy. T4 tumor stage, lymphovascular invasion, perineural invasion, bowel obstruction and/or perforation, <12 harvested lymph nodes, and poor differentiation were defined as high-risk factors. Results. The median age of the patients was 62 years (range 26-88). The median disease-free survival (DFS) was 58.1 months (95% CI, 47.6 months to 68.5 months) in the non-treatment group and has not been reached in the treatment group (P <0.01). In univariate analysis, patient age >60 years and T4 tumor stage were statistically significant factors that affected DFS as poor prognostic factors. Adjuvant chemotherapy reduced the risk of recurrence with statistical significance (P <0.01). In multivariate analysis, patient age >60 years and T4 tumor stage were independent risk factors affecting DFS. In addition, adjuvant chemotherapy was an independent favorable prognostic factor for DFS (P <0.01). Conclusions. Clinical and pathological risk factors in patients with stage II colon cancer may be different in the Turkish population compared to other populations. Further prospective studies in colon cancer are needed to understand the differences in biology and risk factors between races. Copyright - Il Pensiero Scientifico Editore.
Keywords: Adjuvant therapy; Colon cancer; Prognostic factors